Functional Theory of the Development of Religiosity and Knowledge on Intention to Purchase Bubble Tea Drinks in Indonesia - Anggara, Astri Friday Nova; Masnita, Yolanda (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Society competes fiercely to produce the best goods and attract customers with various strategies and methods. Due to high demand, the same phenomenon also occurs in Indonesia, especially in the culinary sector. The food and beverage industry in Indonesia experienced an increase from 2020 to 2021 by 2.54 percent to IDR 775.1 trillion, the Central Statistics Agency (BPS) reported that the national food and beverage industry's gross domestic product (GDP) based on current prices (ADHB) was IDR 1.12 quadrillion in 2021. The type of research used in this research is a quantitative research approach. Data collection was carried out through a Google Form survey tool using the convenience sampling method and structural equation modeling (PLS) which was distributed to 121 respondents. The analysis carried out validity, reliability, Goodness-of-Fit and hypothesis testing. The research results show that there is a positive and significant relationship between the utilitarian function, knowledge and religiosity with Attitude Towards Advertising. Apart from that, this research shows that there is a positive and significant relationship between Attitude Towards Advertising and Retailer Brand on Customer Purchase Intentions. This research also shows that attitude towards advertising can mediate religiosity and knowledge on customer purchase intention.